Design and analysis of robust state constraint control for direct yaw moment control system. (4th July 2022) - He, Youguo; King Ibritam, Ekponoimo; Cai, Yingfeng; Yuan, Chaochun
ABSTRACT: This paper is concerned with the problem of robust constraint control for direct yaw moment control (DYC) system with sideslip angle. A two degree of freedom vehicle dynamics model is considered here. The tangent barrier Lyapunov function (BLFs-Tan) is embedded into the systematic controller design for handling sideslip angle constraint problems. A robust nonlinear constraint control scheme based on BLFs-Tan is proposed not only to track the reference trajectory but also to guarantee no violation on the sideslip angle constraint and refrain from vehicle instability. Simulation results indicate that the proposed scheme can guarantee there will be no violation on sideslip angle constraints and avoid vehicle instability.